IMPORTANCE PERFORMANCE ANALYSIS KUALITAS PELAYANAN BADAN PENGELOLAAN PENDAPATAN DAERAH KOTA BANDUNG - Ahmad Zaini Miftah; Yogi Suprayogi Sugandi; Dedi Sukarno (NATAPRAJA, 2019)
Delivering public service is an important matter where the performance of government institution is equally related to the public satisfactions. This study conducted from nine types of taxes in Bandung Municipal City. Survey has been held to assess the public satisfactions of the tax service performance in Bandung Municipal City for future tax service improvement and innovation to society. Importance-Performance Analysis is being used to measure the service attributes that provided by the authorized government institutions alongside SERVQUAL model from Parasuraman et al. (1985). The results indicate that there is no further handling from the submitted complaint by taxpayers, the limited infrastructure to pay the tax and also the media to convey their dissatisfaction toward current service. Hence, the tax payment system integration is needed which providing tax information base and require procedure to educate the taxpayer and improve accountability of authorized the local government institution.